2021
DOI: 10.1134/s1063776121020114
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Unsteady Bénard-Marangoni Instabilities in Drying Volatile Droplets on a Heated Substrate

Abstract: We study unsteady internal flows in a sessile droplet of capillary size evaporating in constant contact line mode on a heated substrate. Three-dimensional simulations of internal flows in evaporating droplets of ethanol and silicone oil have been carried out. For describing the Marangoni flows we find it necessary to account for the diffusion of vapor in air, the thermal conduction in all three phases and thermal radiation. The equations have been solved numerically by finite element method using ANSYS Fluent.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In parallel, Sefiane et al [13] reported secondary instability in sessile drop evaporating under ambient conditions and later Brutin et al [18] presented a series of experiments on heated droplets exhibiting similar patterns. Multiple researcher reported similar instability under various conditions experimentally [17,19,20,21] and numerical simulation are performed to resolved the secondary instability [22,23,24,25].…”
Section: Introductionmentioning
confidence: 97%
“…In parallel, Sefiane et al [13] reported secondary instability in sessile drop evaporating under ambient conditions and later Brutin et al [18] presented a series of experiments on heated droplets exhibiting similar patterns. Multiple researcher reported similar instability under various conditions experimentally [17,19,20,21] and numerical simulation are performed to resolved the secondary instability [22,23,24,25].…”
Section: Introductionmentioning
confidence: 97%